Biological Column Leaching Of Three Kids Manganese Ore - D. L. Lampshire (Society for Mining, Metallurgy & Exploration, 1993)
Biological leaching using native heterotrophic bacteria was studied by the U.S. Bureau of Mines as a means of extracting manganese from a domestic low-grade wad ore. Column heap leaching simulation techniques were employed using molasses as the nutrient source for the bacteria. These column studies were designed to investigate the effects of molasses medium flow rate, concentration, and replacement interval on the extent and rate of manganese extraction. .Results showed that flow rates between 0.41 and 8.1 L/min/m2 had little impact on manganese extraction. The total amount of molasses used did have a direct effect on the extent and rate of manganese extraction. Manganese extractions over 90-pct were obtained in 12 weeks of bioleaching with 2-week medium replacement cycles.